Analysis of Village Financial Management Based on Permendagri Number 20 of 2018 (Case Study in Wongkai Village, Ratahan Timur Subdistrict) - Ole, Mariska Oktavia; Manossoh, Hendrik; Tangkuman, Steven (Formosa Journal of Applied Sciences, 2024)
According to the Regulation of the Minister of Home Affairs Number 20 of 2018, one of the stages of receiving, storing, depositing/paying, administration, and accountability of village finances is village financial management. The purpose of this study was to determine whether the financial management practices of Wongkai Village, Ratahan Timur Subdistrict, are in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018. This research uses a qualitative descriptive analysis method that refers to previous findings. notes and discussions. The research findings show that the stages of providing financial assistance to villages are fully in accordance with the Ministry of Home Affairs Regulation Number 20 of 2018. There are still obstacles in administration, accountability, depositing, and receiving village funds.